The Effect of Marketing Management and Quality of Education Services on Improving School Reputation - Andi Hendra Paluseri; Thomas S. Kaihatu; Timotius F.C.W Sutrisno; Aida Farzana (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study investigates the effects of Green Market Orientation (GMO) and Management Commitment (MC) on Firm's ESG Performance (FEP), with Aggressive Low Carbon Innovation (ALCI) as a mediating variable. Utilizing a quantitative approach with a correlational design, the study analyzes data from 59 top management in Pertamina group. The Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method was employed to examine complex causal relationships among latent variables, even with a small sample size. The findings reveal that Management Commitment has a significant direct effect on Firm's ESG Performance, while Green Market Orientation significantly influences Aggressive Low Carbon Innovation. However, Aggressive Low Carbon Innovation only mediates the relationship between Management Commitment and Firm's ESG Performance, with no significant mediation observed for the relationship between Green Market Orientation and Firm's ESG Performance. These results underscore the critical role of management commitment in enhancing ESG performance and highlight the need for a more integrated approach to sustainability strategies to maximize the impact of low-carbon innovation. This study contributes to sustainability-related literature by demonstrating how internal firm factors, such as green market orientation and management commitment, affect the successful implementation of ESG strategies. Future research should consider additional factors, such as policy support, industry-specific dynamics, and green technology adoption, to strengthen the relationships among these variables and enhance ESG outcomes.